(untitled) (Journal of Scientific Research, 2022)
This paper deals with a mathematical model that represents non-Newtonian bile flow through a calculus duct under the influence of heat transfer with wall slip conditions. The peristaltic flow of bile is characterized by a generalized Carreau’s model. An ordinate transformation is initiated to map the cosine geometry of the stone into a rectangular grid. It allows evaluation velocity, pressure distribution, flow rate, and reflux occurrence conditions, adopting the perturbation technique, the analytical solution obtained under various parameters, such as Knudsen number, amplitude ratio, Grashof number, Weissenberg number, and power index. These mathematical expressions are analyzed by plotting the graph in MATLAB R2018b software and observed that the axial velocity and the pressure gradient are strongly affected by heat and wall slip parameters.